2017
DOI: 10.1007/978-3-319-64804-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Stressors in Atopic Dermatitis

Abstract: As with other inflammatory skin disorders, atopic dermatitis has a tendency to cause stress and also be exacerbated by it. Patients with atopic dermatitis have several disease-associated stressors, some of which include physical discomfort due to itching and altered appearance due to flare-ups. These stressors have been shown to effect patients psychosocially by altering sleep patterns, decreasing self-esteem and interfering with interpersonal relationships. In combination with its direct effect on patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…These stressors have been shown to impact other quality of life domains, altering sleep patterns, decreasing self-esteem and interfering with interpersonal relationships. 18 It is worth noting that AD financial impact has been reported by our patients as a highly relevant factor, comparable to routine alterations, pain and anxiety. Nearly one fourth of surveyed participants have no healthcare insurance, leading to a low accessibility to treatment due to their high costs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These stressors have been shown to impact other quality of life domains, altering sleep patterns, decreasing self-esteem and interfering with interpersonal relationships. 18 It is worth noting that AD financial impact has been reported by our patients as a highly relevant factor, comparable to routine alterations, pain and anxiety. Nearly one fourth of surveyed participants have no healthcare insurance, leading to a low accessibility to treatment due to their high costs.…”
Section: Discussionsupporting
confidence: 55%
“…17 In addition, it is highlighted that AD induces stress, but can also be exacerbated by it. 18 Several AD-associated stressors have been described, including physical discomfort due to itching and altered appearance during AD flare-ups. These stressors have been shown to impact other quality of life domains, altering sleep patterns, decreasing self-esteem and interfering with interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children whose skins are disfigured by AD often experience discrimination or stigmatisation (Chernyshov, ). Previous research has suggested that children living with AD have behavioural problems and experience psychological disturbances, especially psychological stress (Barilla, Felix, & Jorizzo, ), anxiety, depression (Cheng et al, ) and attention deficit hyperactivity disorder (ADHD; Lee et al, ). Generally, children living with AD have a significantly lower quality of life than their healthy peers (Lifschitz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, optimal AD mouse models should be predictive for clinical treatment outcomes, should permit to elucidate which key signals suffice to induce AD lesions in healthy human skin in vivo and to trigger AD lesions by psychoemotional (perceived) stress 4 -just as in many AD patients, 5,6 in whom psychological interventions can be beneficial. [7][8][9] These desirable prerequisites of clinically relevant AD mouse models 4 favor the use of human skin xenografts on immunocompromised mice.…”
Section: Introductionmentioning
confidence: 99%